Forming the Skills of Asking Questions (from the Experince of Foreign Medical Students’ Langauge Training) - Tamozhska, Iryna (Educological discourse, 2023)
The article introduces a system of exercises (conditionally communicative, situationally conditioned communicative) developed by the author for the formation of the ability to pose questions (to ask). The tasks were performed in oral / written form by foreign students of the medical faculty. It is stressed that this type of activity is quite an effective didactic tool used for language training of foreign medical students to develop their ability to ask different types of questions (open, closed, clarifying), which promotes dialogic communication between medical specialists and patients / colleagues. The exercises are supplemented with instructions, tables / examples / theoretical material. It is found out that foreign medical students’ ability to ask questions is grounded on available thorough knowledge at the level of professional communication, in particular medical terminology, theoretical knowledge about various types of questions, acquired communicative and speech experience during practical training in health care institutions, as well as the following skills: 1) combine language units in a correct way; 2) determine the purpose of the inquiry in accordance with the content of the communication / professional and communicative situation; 3) predict / guide the possible answers of the patient / his relatives / specialists in the medical field, which clarify / expand the available knowledge in accordance with the inquiry. It is worth mentioning that medical terms (types of diseases, symptoms, complaints, nature of pain, medicines, organs and parts of the human body) in interrogative sentences mark simulated professional and communicative situations, determine the semantic and conceptual unity of the statements of medical professionals and their patients / colleagues. The proposed educational and methodological support (conditional communicative, situationally conditioned communicative exercises) contributes to the expanding foreign medical students’ vocabulary with active and passive terminological vocabulary, as well as to the conscious usage of professional vocabulary in «question – answer» structures during simulated dialogic practice according to various models (a doctor ⟷ a patient, a doctor ⟷ a colleague). The methodological developments presented in the article involve raising awareness of the need to acquire the skills of asking questions for effective dialogic communication between medical professionals and their patients / patients’ relatives/ colleagues.